A review of thin film solar cell - Aziz, Issa M (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Due to the recent surge in silicon demand for solar modules, thin-film photovoltaic modules have an opportunity to join the market in considerable numbers. For the corresponding technologies, the dependability, accessibility of cell materials, and comparison of various attributes are all examined. A few crucial elements and solutions for future development are also highlighted with regard to the new solar cell technology. The condensed section of this comparison study aims to assist readers in understanding potential research areas taking into account appropriate solar cell production and application methods.